(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
“Mathematical and software support for computers, complexes and computer networks” is a specialty that deals with the development of mathematical theory of programming, the creation, maintenance and operation of software for various purposes for computers and computer systems, as well as complexes built on their basis, computer and neural networks , characterized in that it includes theoretical and experimental research in the field of software tools for organizing and managing the processing of data and knowledge, the creation of applied mathematical software, software tools for automating program development and human-computer communication. The following article is devoted to mathematical and software support for computers, complexes and computer networks.